Utilization of Databases in Planning the Preaching of the Muhammadiyah Regional Leadership of Medan City - Rahul Nasution; Nurhanifah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to analyze the use of databases in planning da'wah in the Muhammadiyah Regional Leadership (PDM) of Medan City. Integration of information technology, especially the use of databases, is seen as an important tool for increasing effectiveness and efficiency in da'wah management. This research uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observation and documentation. The research results show that the use of a database allows Medan City PDM administrators to manage data in a more structured and systematic manner, which in turn supports decision making that is more precise and relevant to the needs of the congregation. The database also facilitates monitoring and evaluation of da'wah programs, as well as increasing transparency and accountability in the implementation of da'wah activities. However, this research also identified several challenges, such as limited resources and adaptation to technology. Nevertheless, Medan City PDM shows a strong commitment to overcoming these challenges and optimizing the use of databases in missionary planning. Overall, the use of databases has been proven to support da'wah planning that is more effective and responsive to social dynamics.